Influence of Organisational Capability and Knowledge Sharing on Performance at Eskom Distribution - Mampuru, Thabo Mothobi (University of the Witswatersrand, Johannesburg, 2024)
This research report is about how organisational capability and knowledge sharing influence performance in a South African power utility organisation, namely Eskom Distribution division. Organisational capability in this report means the ability and capacity to do maintenance on the existing infrastructure, network, and equipment to have a sustainable and consistent electricity distribution. Electrical system maintenance has gained attention from both researchers and practitioners over the past few years due to, among other things, constant load shedding that affects the social and economic aspects of South Africa. To this point improving electrical system reliability and reducing maintenance costs are top priorities of a power utility, notably Eskom Distribution (ED). Knowledge sharing is the transferring of the know-what and the know-how of doing maintenance, from one person to the next; that is, the research problem is that transferring of experience, skills, and information among employees is still a key issue at the Power Utility. The purpose of the study was, thus, to explore and describe organisational capabilities and knowledge-sharing enablers and challenges, using Resource- based theory (RBT) and Social-exchange theory (SET) as theoretical lenses. Improved performance is inferred to be when there is less downtime, less failure of equipment due to good maintenance and restoration time of electrical supply, achieved without compromising the safety of personnel and equipment. The study was conducted following an interpretive research philosophy and a case study was employed as a research strategy to get an in-depth understanding of ways that could be used to improve organisational performance. Semi- structured interviews were conducted with managers, engineers, technicians, and artisans as study participants. In the present study, one way to improve performance is the understanding of resources and behaviour, especially how maintenance strategies are formulated and how knowledge sharing could happen among employees to subsequently enhance and effect performance. The study found that managers play a key role in designing organisational capability and that they should affect knowledge sharing through various internal processes. The outcome and the contribution of iii the study is a conceptualised framework that may help improve performance through an enhanced knowledge sharing and organisational capability, in the context of the Power Utility, Eskom distribution division
A research report submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Energy Leadership
Keywords: Organisational Capability; Knowledge Sharing; Maintenance; Performance; Social Exchange Theory; Resource-Base Theory; UCTD; SDG-7: Affordable and clean energy